Pharmacokinetics of ceforanide. - Ripa, S (1982)
The pharmacokinetic of ceforanide, a new parenteral cephalosporin antibiotic, were examined at intravenous and intramuscular doses of 250, 500, and 1,000 mg in healthy male volunteers. Over the above dosing range, ceforanide pharmacokinetics were essentially linear, with plasma clearances varying from 2.2 to 2.5 liters/h. The best present overall estimate of the drug's half-life was 2.9 h. Intramuscular ceforanide was 100% bioavailable, Peak intravenous serum levels were 39, 71, and 135 micrograms/ml at the end of 30-min infusions of 250, 500, and 1,000 mg; after intramuscular injections of 250, 500, and 1,000 mg, the respective peak serum levels were 21, 38, and 69 micrograms/ml. From 80 to 85% of the above doses were eliminated as unchanged.